The strategy of the CGIAR system-wide genetic resources programme - International Plant Genetic Resources Institute; CGIAR Systemwide Genetic Resources Programme (1999)
This brochure provides an introduction to the CGIAR System-wide genetic resources programme's five thematic areas. These five areas are: policy, public awareness, information, knowledge and technology and capacity building.